The effect of high yttrium solute concentration on the twinning behaviour of magnesium alloys. (1st January 2015) - Stanford, N.; Marceau, R.K.W.; Barnett, M.R.
Abstract: The deformation behaviour of two single phase binary alloys, Mg–5Y and Mg–10Y, have been examined. In compression, two twin types were observed, the common 1 0 1 ¯ 2 twin as well as the less common 1 1 2 ¯ 1 extension twin. It is shown that the 1 1 2 ¯ 1 twin is much less sensitive to solute concentration than the 1 0 1 ¯ 2 twin, and it is suggested that the simple atomic shuffle of the 1 1 2 ¯ 1 twin reduces the solute strengthening imparted by Y additions. The common 1 0 1 ¯ 2 twin showed significant hardening as a result of alloying with Y. An analysis of solute behaviour has indicated that of the four chemical parameters investigated, i.e. atomic size, shear modulus, electronegativity and solute distribution, it appears to be the larger atomic radius of Y compared to Mg that increases the stress required to activate the 1 0 1 ¯ 2 twin. It is suggested that the large atomic radius inhibits the atomic shuffling process which accompanies the twinning shear in this twin type.